Analisis Faktor-faktor Produksi pada Peternakan Sapi Perah Ompie Farm di Kabupaten Tanah Datar - - Syafril; R. Wati; A.I. Osvaldo (Universitas Andalas, 2011)
The research purpose was analyzed the utilization of production factors in dairy cow farming in economies of scale at Ompie dairy cow farming in Tanjung Bonai village, North of Lintau Buo subdistrict, Tanah Datar regency. The samples were 18 lactating dairy cows. Data obtained through case study by observing and calculated the consumption of grass and concentrate as well as the lactating month and the cow’s weight directly, and interviewed Farm’s caretaker. Production factors estimated by using ordinary least square by using SPSS 17. Result shown, production function Y= 0,0012 H1,671K0,405M-0,187W0,119 was obtained. R Square test determination, coefficient (R2) was 0.721, which was means 71,2% of production variation can be explained through green food variable, concentrate, month of lactation, and different cows’ weight. The F test showed that overall, independent variables has significant impact on milk production (P<0,01). The t test result showed that green foods variable and month of lactation has real impacts on level of trust 99% while concentrate and cow’s weight did not have significant impact. This farm is experiencing increasing return to scale which means increasing the amount of input will generate additional output with bigger proportion. We can observe this on Σbi value of 2,076.